The role of women in community life in forest villages: The example of Isparta Forest District - Sibel Korkmaz; Hasan Alkan (Turkish Journal of Forestry, 2015)
The purpose of the study is to make determinations on the roles that the rural women living in forest villages have on economic, social and cultural life. The object of the study is the women living in forest villages located within the Forest Sub-District Directorate of Isparta. In this context, the survey study was conducted with 222 women. Other data gathering methods used in the study was literature analysis, interviews and observations. The percentage ratios were used to evaluate the data obtained within the scope of the study and the chi-square test was utilized to determine the relationship between the variables. According to the results of study, it was determined that the women have a very heavy workload in economic life. It was also determined that most women made to work, within the context of unpaid family workers, are deprived of social security. The role of women in social life is very important as well. Almost all of the work of the house being used as a daily life area is on the women. In addition, women’s participation in decision processes of both economic and social contexts is at a very low level. It was determined that the non-formal education activities are not sufficient either. When the employment opportunities from the forest resources where examined, it was seen that most women in the region were made to work in plantation, youth care and plant nursery work. A large portion of women consider forest labor to be an appropriate work group for them. The presence of positive perception towards environmental forest resources is very important in terms of the relationships the women have with natural resources. A significant portion of women in the region being satisfied with their lives is another important result of the study.